NiCo@SiO2 core-shell catalyst with high activity and long lifetime for CO2 conversion through DRM reaction. (March 2018) - Zhao, Yu; Li, Hui; Li, Hexing
Abstract: A novel NiCo@SiO2 core-shell catalyst with single NiCo alloy nanoparticle encapsulated by SiO2 shell was synthesized by microemulsion method. During dry reforming of CH4 with CO2 (DRM) reaction, this catalyst exhibited high activity and selectivity, superior over either the Ni@SiO2 or the Co@SiO2 core-shell catalyst or the NiCo/SiO2 supported catalyst. The CO2 and CH4 (1:1) could be absolutely converted into CO and H2 with molar ratio around 1:1. More importantly, this catalyst displayed very long lifetime (> 1000 h) in the DRM reaction at 800 °C, much better than either the Ni@SiO2 or the Co@SiO2 core-shell catalyst or the NiCo/SiO2 supported catalyst. Kinetic studies revealed that the catalyst with small metal nanoparticle size exhibited higher activity, which could also inhibit carbon deposition. The encapsulation of metal nanoparticles by SiO2 shell could effectively inhibit the agglomeration of active sites. Meanwhile, the enhanced activity of NiCo alloy catalyst could also diminish the surface carbon deposition. Therefore, the NiCo@SiO2 core-shell catalyst displayed excellent stability in DRM reaction, showing good potential in industrial application. Graphical abstract: fx1 Highlights: A novel NiCo@SiO2 core-shell catalyst was synthesized by microemulsion method. The obtained catalyst exhibited high activity and long lifetime in the DRM reaction. The mechanism and anti-coking ability with various sized nanoparticles was explored.